Pain in the context of urgency and emergency: an integrative review (Research, Society and Development, 2020)
Studies have shown that pain is one of the main complaints of patients who are seen at the Urgency and Emergency Units, with vital signs being evaluated and, in addition, the severity of pain for later classification and follow-up of care. The objective was to analyze scientific production regarding pain management in the face of urgency and emergency. For this purpose, a descriptive integrative literature review was carried out, and the search for scientific articles was carried out in the SciELO database and virtual library, using the terms: "pain", "urgency and emergency", in all the fields, and “nursing” in the area of knowledge. The main results showed pain assessment in the face of urgency and emergency, analyzing the degree of pain during the reception of the patient for further classification, medical care and being medicated according to medical prescription and monitoring pain relief after analgesics.